Una nueva especie de Batrachyla (Anura: leptodactylidae: telmatobiinae) de Argentina : Relaciones filogéneticas interespecíficas - Basso, Néstor Guillermo (1994)
A new species of telmatobiinae leptodactylid frog genus Batrachyla is described from the Nothofagus forest of Chubut province, Southern Argentina. Batrachyla fitzroya sp. nov. is more closely related to B. antartandica than to any other species of the genus. A cladistic analysis of the genus Batrachyla applying parsimony is presented using morphological and osteological characters. Polarity was based on the outgroup comparison method. The data were analysed using Farris's phylogenetic program Hennig86, using the implicit enumeration option. In the preferred phylogeny B. taeniata is the sister species of the clade B. leptopus-(B. antartandica-B. fitzroya).